2002
DOI: 10.1089/088282402320914610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anti-HIV Seropositivity in Myanmar Migrators in a Rural Area of Thailand

Abstract: Although the prevalence of anti-HIV seropositivity in the Thai population has decreased in the recent years, migration of Myanmar labors as carriers into Thailand may increase the prevalence of anti-HIV seropositivity. Screening is recommended for the Myanmar migrators. Of interest, the epidemiology of anti-HIV seropositivity in Myanmar migrators has not been precisely determined. In this study, we report the prevalence of anti-HIV seropositivity in Myanmar migrators in a rural community in the Southern Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Nevertheless, this survey has led to a shift in the PMTCT programme within Mae La refugee camp in order to overcome this gap, to 'opt-out' of HIV testing, rather than to 'opt-in'. Migration, identified here as seeking work outside the camp, is a co-factor for HIV infection in south-east Asia 9,11 and was identified both by the PMTCT counsellors and by the women themselves. Working outside the camp is a new context from the traditional, controlled and protective environment of the refugee camp or a rural village in Burma.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this survey has led to a shift in the PMTCT programme within Mae La refugee camp in order to overcome this gap, to 'opt-out' of HIV testing, rather than to 'opt-in'. Migration, identified here as seeking work outside the camp, is a co-factor for HIV infection in south-east Asia 9,11 and was identified both by the PMTCT counsellors and by the women themselves. Working outside the camp is a new context from the traditional, controlled and protective environment of the refugee camp or a rural village in Burma.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al, 2005; Maxwell et al, 2006; Yang, Derlega, & Luo, 2007), and actual HIV infection (Wiwanitkit & Waenlor, 2002; Zehender et al, 2004; Zuma, Gouws, Williams, & Lurie, 2003). Integration into the society of destination is one of the strategies which may assist individual migrants in avoiding negative health consequences (Chen X et al, 2008 and 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Risky sexual behaviour and high prevalence of HIV [3.2% to 16.1%] has previously been documented among fishermen groups [ 5 - 9 ]. Often fishermen communities have higher prevalence of HIV compared to the general population [ 6 , 10 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of fishermen communities by Alison and Seeley suggested that their vulnerability to HIV stems from complex, interacting causes that may include the time fishermen spend away from home, their high mobility, their access to daily cash income in an overall context of poverty, their background characteristics, the ready availability of commercial sex in fishing ports and risk taking behaviors [ 8 ]. Factors such as young age, unmarried status, multiple sex partners including commercial sex partners, duration of stay in the port areas, lack of condom use, and prevalence of sexual violence have been found to be associated with increased vulnerability of fishing communities to HIV infection [ 5 , 9 , 11 ]. Since some studies in fishing communities have reported high HIV prevalance in women [ 5 , 10 ], it is assumed that heterosexual transmission prevails as a source of infection in such communities.…”
Section: Introductionmentioning
confidence: 99%